1990
DOI: 10.1128/jcm.28.5.843-850.1990
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection and identification of enteroviruses using enzymatic amplification and nucleic acid hybridization

Abstract: Analysis of enteroviral genomes has revealed that the 5' nontranslated region is highly conserved, providing consensus sequences for the design of oligonucleotides which should anneal to most, if not all, human enteroviral RNAs. We designed and used a pair of such generic primers to enzymatically amplify cDNA from coxsackievirus group B types 1 through 6, poliovirus types 1 through 3, 4 coxsackievirus A types, and 29 echoviruses. The polymerase chain reaction (PCR) products generated with these enteroviral pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
77
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(83 citation statements)
references
References 42 publications
(48 reference statements)
6
77
0
Order By: Relevance
“…The RMA was more sensitive than culture in detecting HRV, EnV, and Ad and more sensitive than immunofluorescent-antibody techniques in detecting RSV ( Table 5). These results are consistent with previous reports that culture could not detect many HRV and EnV strains/serotypes with fastidious growth requirements (5,8,17,39,45) and confirmed that immunofluorescent-antibody methods are less sensitive than PCR in detecting RSV (5,8,17,39,45).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The RMA was more sensitive than culture in detecting HRV, EnV, and Ad and more sensitive than immunofluorescent-antibody techniques in detecting RSV ( Table 5). These results are consistent with previous reports that culture could not detect many HRV and EnV strains/serotypes with fastidious growth requirements (5,8,17,39,45) and confirmed that immunofluorescent-antibody methods are less sensitive than PCR in detecting RSV (5,8,17,39,45).…”
Section: Discussionsupporting
confidence: 93%
“…Culture has been and still is considered the gold standard for diagnosis of respiratory viruses because it can be used for a wide spectrum of viruses and can detect as little as 1 infectious unit. However, viral culture often takes 2 to 3 weeks to complete and has limited ability to detect viruses that have fastidious growth requirements, such as CoV, MPV, and many serotypes of HRV and EnV (5,8,17,39,45). Immunofluorescent staining is fast, providing results within several hours, but assay sensitivity and the availability of antisera can be limiting factors (17,39).…”
Section: Discussionmentioning
confidence: 99%
“…Detection of enteroviruses by RT-PCR, semi-nested PCR and DNA hybridization Enteroviral cDNA was transcribed from 10 ll RNA extract by RT with random hexamers and the cDNA amplified by the PCR as described previously (Greening et al 1999). Pan-enteroviral primers ENT1 (reverse, complementary to positions 622-640) and ENT2 (forward, 446-460) from the conserved 5¢ noncoding region (Chapman et al 1990) produced a DNA product of 196 bp. RT-PCR products were analysed by 2% agarose gel electrophoresis, stained with ethidium bromide and visualized by UV light.…”
Section: Molecular Methodsmentioning
confidence: 99%
“…For the environmental samples, 3 ll of extracted RNA was used for the enterovirus-specific RT-PCR using the primers E1 and E2 to amplify the conserved 5¢UTR as described previously (Chapman et al 1990). The reverse transcription and PCR steps were performed in a single tube by using the one-step RT-PCR kit from Qiagen, according to the manufacturer's instructions (Hilden, Germany).…”
Section: Rt-pcr and Genotypingmentioning
confidence: 99%